Notorious RBG : the life and times of Ruth Bader Ginsburg - Carmon, Irin; Knizhnik, Shana (DEY ST., an Imprint of William Morrow Publishers, 2015)
Supreme Court Justice Ruth Bader Ginsburg never asked for fame -- she was just trying to make the world a little better and a little freer. But along the way, the feminist pioneer's searing dissents and steely strength have inspired millions. Notorious RBG takes you behind the myth for an intimate, irreverent look at the justice's life and work. As America struggles with the unfinished business of gender equality and civil rights, Ginsburg stays fierce. And if you don't know, now you know.